Linking regional autonomy-embeddedness value orientation and innovation - Vladyslav Soloviov (Journal of Innovation and Entrepreneurship, 2022)
Culture, as a key driver of innovative activity, has been largely analysed at the national and organisational levels by interdisciplinary studies. This article investigates the relationship between Schwartz's cultural dimensions and innovation, proxied by the number of patent applications to the European Patent Office, at the regional level. Using European Social Survey questionnaire, Eurostat and European Patent Office data and employing factor analysis and multilevel models, the link between culture and innovation is examined for regions of 26 European countries. The results of the analysis show that cultural differences are significantly related to differences in patenting even between regions of the same country. In particular, a higher autonomy-embeddedness score is significantly positively linked to patent applications at the regional level. The study highlights the usefulness of region-level cultural dimensions, providing evidence of more precise results obtained when these dimensions are used in the analysis.
Keywords: 650; European Social Survey; Patents; Regional culture; Value orientations